2015
DOI: 10.17269/cjph.106.5053
|View full text |Cite
|
Sign up to set email alerts
|

The correlates of current smoking among adult Métis: Evidence from the Aboriginal Peoples Survey and Métis Supplement

Abstract: OBJECTIVE: To examine the correlates of current smoking among Métis aged 18 years and older, with a particular focus on culturally-specific factors. Cultural factors included spirituality, knowledge of an Aboriginal language, membership in a Métis organization and attendance at Métis cultural events. Demographic, geographic, socio-economic and health-related variables were also considered.METHODS: Data from 6,610 adult Métis aged 18 years and older who responded to the 2006 Aboriginal Peoples Survey and Métis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Based on a priori findings demonstrating associations to self-perceived general and mental health, covariates included age, sex, education, income, identity, residential school attendance, language spoken, smoking, and alcohol use ( 42 , 44 , 48 ). Sex was reported dichotomously (male and female) in the 2012 APS and was reported as “Male,” “Female,” “Valid Skip,” “Don't Know,” “Refusal,” and “Not Stated” in the 2017 APS.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on a priori findings demonstrating associations to self-perceived general and mental health, covariates included age, sex, education, income, identity, residential school attendance, language spoken, smoking, and alcohol use ( 42 , 44 , 48 ). Sex was reported dichotomously (male and female) in the 2012 APS and was reported as “Male,” “Female,” “Valid Skip,” “Don't Know,” “Refusal,” and “Not Stated” in the 2017 APS.…”
Section: Methodsmentioning
confidence: 99%
“…However, all 2017 responses were either “Male” or “Female” thus only responses of “Male” or “Female” were included in analyses. Education was trichotomized as “less than high school,” “high school or equivalent,” and “more than high school” to correspond with similar studies ( 42 , 44 , 49 ). The seven APS levels of income were collapsed to four: “ < $10,000,” “between $10,000–$30,000,” “between $30,000–$50,000,” and “$50,000 and more” in the previous year to align with Statistics Canada's 2011 Low-Income Cut-Offs ( 50 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This necessity of context has been noted in relation to both individual-and community-level data. King (2015) emphasized the requirement of focus groups or discussion circles to provide frame of reference for the findings from a study by Ryan, Cooke, Leatherdale, Kirkpatrick, and Wilk (2015) that traditional language use is related to smoking. Walls, Whitbeck, and Armenta (2016) actually carried out the recommendation touted by King (2015) and this paper and demonstrated that the relationships between Aboriginal spirituality and poorer psychological outcomes were reduced once perceived discrimination and historical losses were accounted for statistically.…”
Section: Introductionmentioning
confidence: 99%